Pulmonary nodules in African migrants caused by chronic schistosomiasis. Issue 5 (May 2017) - Gobbi, Federico; Buonfrate, Dora; Angheben, Andrea; Beltrame, Anna; Bassetti, Matteo; Bertolaccini, Luca; Bogina, Giuseppe; Caia, Simone; Duranti, Silvia; Gobbo, Maria; Marchese, Valentina; Marocco, Stefania; et al.
Summary: Schistosomiasis is a neglected tropical disease that can cause mainly hepatic and genitourinary damage, depending on the species. Involvement of the lungs has been commonly described in acute infection (Katayama syndrome) and chronic infection (pulmonary hypertension). Although rarely reported in the scientific literature, cases of lung nodules due to chronic schistosome infection are also possible and are probably more frequent than commonly thought. Here we report seven cases of African migrants who were diagnosed with chronic schistosomiasis and pulmonary nodules due to deposition of schistosome eggs, and we compare our findings to the case reports found in the scientific literature. We discuss the management of these patients in a non-endemic setting, beginning with a first fundamental step that is to include parasitic infections, namely schistosomiasis, in the differential diagnosis of pulmonary nodules in African immigrants. All patients responded to antiparasitic treatment with praziquantel after a relatively short time. We therefore conclude that lung biopsies and other invasive procedures (performed in the first cases to rule out other potential causes, such as tuberculosis or malignant nodules) can be avoided or postponed.